Über den Steringehalt pflanzlicher Mikrosomen - W. Eichenberger (CHIMIA)
The composition of microsomal lipids from Spirodela oligorrhiza L., Lactuca sativa L., and Allium porrum L. plants was investigated. Contamination by chloroplast lipids was calculated and eliminated, giving the lipids of “chloroplast-free microsomes” (CFM). These lipids originate from the endoplasmic reticulum and contain 6 to 14% sterol compounds and 38 to 45% phospholipids. On a total lipid base the sterol content is of the same range in microsomes of both plant and animal origin. The ratio of sterol compounds to phospholipids in plant microsomes is 0.14 to 0.33 compared to 0.07 to 0.17 in liver microsomes. These results suggest that sterol compounds represent an essential part of the lipids of both plant and animal microsomes.